태아형성에 따른 임신맥의 변화에 대한 연구 - 이혜연(Hye Yeon Lee); 김병수(Byung Soo Kim); 강정수(Jung Soo Kang) (동의생리병리학회지, 2009)
Nowadays we can take a physical examination during pregnancy by various and advanced technology instruments. But there were no instruments in old times, so the ancient doctors examined symptoms and pulse of a pregnant woman. Therefore it is very important to comprehend the pulse in Oriental medicine. Fetus and mother are connected with the umbilical cord, and they interact with each other. Especially, symptoms and pulse of mother change during the formation of fetus. On account of being easy to study the changes of pulse from pregnant woman, it is important to know the formation of fetus. In Western medicine, the Buddhist scriptures and Oriental medicine mentioned about the formation of fetus. Because of different viewpoints, the choice of words and formative methods are differ from field to field. Western medicine calls the formation of fetus 'development', the Buddhist scriptures call it 'Ru-tai', and oriental medicine calls it 'Yang-tai'. In spite of the different viewpoints, they have supplementary explanations to study fetus. As a result, we can understand the reasons why pregnancy pulse cannot help changing from month to month.